2021
DOI: 10.3390/infrastructures6020016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Forest Fires on Interconnected Critical Infrastructures under Climate Change. Evidence from South France

Abstract: The present work introduces a case study on the climate resilience of interconnected critical infrastructures to forest fires, that was performed within the framework on H2020 EU-CIRCLE project (GA 653824). It was conducted in South France, one of the most touristic European regions, and also one of the regions at the highest forest fire risk that is projected to be amplified under future climate conditions. The case study has been implemented through a co-creation framework with local stakeholders, which is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Natural hazards affecting electricity infrastructures in hinterland regions can disrupt electricity supply in distant city areas. For example, modeling electricity networks has shown that fires in the hinterlands threaten distribution of electricity to customers far away (Sfetsos et al 2021). In another study, it is revealed that a lack of precipitation can decrease electricity production from hydroelectric dams, which in turn decreased electricity supply to dependent, often urban, areas (Kreimer et al 2003).…”
Section: Electricity Generation and Transmissionmentioning
confidence: 99%
“…Natural hazards affecting electricity infrastructures in hinterland regions can disrupt electricity supply in distant city areas. For example, modeling electricity networks has shown that fires in the hinterlands threaten distribution of electricity to customers far away (Sfetsos et al 2021). In another study, it is revealed that a lack of precipitation can decrease electricity production from hydroelectric dams, which in turn decreased electricity supply to dependent, often urban, areas (Kreimer et al 2003).…”
Section: Electricity Generation and Transmissionmentioning
confidence: 99%
“…It is increasingly important to examine the economic and social consequences of forest fires. Studies have been conducted on the impact of fires on the economy [18][19][20][21][22], employment [23,24], and the cost of damage to infrastructure [25][26][27][28], buildings [29][30][31], and homes [32][33][34][35][36], and also how different building materials and the location on the perimeter of buildings respond to fire [37][38][39][40]. All of these works, with varying objectives, methodologies, and areas of study, enable us to partially comprehend the causality and consequences of fires.…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly important to examine the economic and social consequences of forest fires. Studies have been conducted on the impact of fires on the economy [18][19][20][21][22], employment [23,24], and the cost of damage to infrastructure [25][26][27][28], buildings [29][30][31], and homes [32][33][34][35][36]. All of these works, with varying objectives, methodologies, and areas of study, enable us to partially comprehend the causality and consequences of fires.…”
Section: Introductionmentioning
confidence: 99%